2013
DOI: 10.1093/ntr/ntt130
|View full text |Cite
|
Sign up to set email alerts
|

Complete Home Smoking Bans and Antitobacco Contingencies: A Natural Experiment

Abstract: The California antitobacco culture may have influenced home smoking bans in Mexico. Based on the Behavioral Ecological Model, exposure to socially reinforcing contingencies or criticism may explain adoption of home smoking bans in Tijuana, Mexico, approximating rates relative to San Diego, California, and higher than those in Guadalajara, Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It is also possible that there is an effect if neighbouring countries adopt stronger tobacco control policies. Hovell et al 39 examined the influence of socially reinforcing contingencies on adoption of in-home smoking bans among Mexican adults living in the USA (San Diego) and Mexico (Tijuana and Guadalajara). They found that while the prevalence of smoking bans was highest in San Diego (91%), residents of Tijuana, which is just over the border with California, were significantly more likely to have an in-home smoking ban (66%) than residents of Guadalajara (39%), which is hundreds of miles away from the border.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that there is an effect if neighbouring countries adopt stronger tobacco control policies. Hovell et al 39 examined the influence of socially reinforcing contingencies on adoption of in-home smoking bans among Mexican adults living in the USA (San Diego) and Mexico (Tijuana and Guadalajara). They found that while the prevalence of smoking bans was highest in San Diego (91%), residents of Tijuana, which is just over the border with California, were significantly more likely to have an in-home smoking ban (66%) than residents of Guadalajara (39%), which is hundreds of miles away from the border.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural level factors reflect ethnicity and acculturation. Variations of these models have been previously used for Chinese, Korean and South Asian American populations to understand tobacco‐related behaviours .…”
Section: Methodsmentioning
confidence: 99%
“…This decrease in physical activity, coupled with an abundant food supply that is energy dense and relatively inexpensive, has led to substantial increases in obesity; one-third of adults and approximately 17% of children are now classified as obese (Flegal, Carroll, Ogden, & Curtin, 2010). Ecological approaches to population behavior management, similar to those that have reduced tobacco use (Hovell & Hughes, 2009; Hovell et al, 2013), can be used to increase both recreational and lifestyle-related physical activity (Sallis, Cervero, Henderson, Kraft, & Kerr, 2006). …”
mentioning
confidence: 99%